PREVENTIVE PAEDIATRICS — NEW CHALLENGES - A. A. Baranov; L. S. Namazova-Baranova; V. Yu. Al’bitskii (Вопросы современной педиатрии)
The article takes up priority directions of preventive paediatrics concerning health formation of rising generation, organization of health care for children, decrease of morbidity, disability and mortality rate. The authors mention the importance of vaccination in control of the most common infections, base the necessity of complex rehabilitation health care system organization for disable children and need of wide spreading of developed and used in practical Russian health care types and methods of prophylaxis of rare (orphan) diseases. The ways of prophylaxis, maintenance, strengthening and recovery of children’s health are suggested in this article.